Consumption patterns of social assistance (Bansos) recipients in the Bangka Belitung Islands Province - Devi Valeriani; M. Faisal Akbar; Rusdi Rusdi; Mardani Mardani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
Poverty is one of the main problems in economic development, and various efforts are made to improve and expand social assistance programs (Bansos). This study aims to analyze the consumption patterns of Bansos recipients in Bangka Belitung Province. The data used are secondary data from various related agencies and primary data sourced from surveys on Bansos recipient households. The scope of the research covers two districts with the highest and lowest number of beneficiary households in the Province of Bangka Belitung Islands. The analytical method used is linear regression analysis. The results showed that Bansos significantly affected public spending, especially food spending, cellphone credit, and business capital. On the other hand, the provision of Bansos does not significantly affect expenditures such as non-food consumption, education, health, cigarettes, and debt payment